2004
DOI: 10.1299/jsmeb.47.804
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Casing Treatment Configuration

Abstract: Circumferential grooves over a rotor blade tips are used for improving axial flow compressor performances. Such casing treatment facility extends a stable operation range in most cases, but decreases compressor efficiency as a rule. There are presented results of parametric investigation of grooves of traditional and new configurations. Development of new groove constructions must permit combining of stable operation range extension with efficiency increase. Model on basis of Group Method of Data Handling may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Compared with the active control method, the passive control method has the advantages of simple structure, easy implementation and significant enhancing stability effect, so it is favored by the majority of researchers. However, numerous research results have shown that while the passive control method improves the compressor stall margin, it often causes a decrease in compressor efficiency (Hembera and Danner 2008;Rabe and Hah 2002;Bailey 1972;Fujita and Takata 1984;Takata and Tsukuda 1977;Moore et al 1971;Nezym 2004;Wilke and Kau 2002). Therefore, looking for a flow control method while improving the compressor stall margin, it has little effect on the compressor efficiency, that is the goal pursued by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the active control method, the passive control method has the advantages of simple structure, easy implementation and significant enhancing stability effect, so it is favored by the majority of researchers. However, numerous research results have shown that while the passive control method improves the compressor stall margin, it often causes a decrease in compressor efficiency (Hembera and Danner 2008;Rabe and Hah 2002;Bailey 1972;Fujita and Takata 1984;Takata and Tsukuda 1977;Moore et al 1971;Nezym 2004;Wilke and Kau 2002). Therefore, looking for a flow control method while improving the compressor stall margin, it has little effect on the compressor efficiency, that is the goal pursued by the researchers.…”
Section: Introductionmentioning
confidence: 99%
“…But adopting the passive control methods while improving the SM of the compressor often causes the compressor efficiency to drop. [3][4][5][6][7][8][9][10][11][12][13] The blade tip recess (BTR) was used on the turbine blade to cool the turbine blade; it has been widely used and studied on the turbine blade. [14][15][16][17][18][19][20] While the application and research of the BTR on the compressor blade is relatively less, Gourdain and Leboeuf 21 conducted a study on the BTR to suppress the compressor rotating stall in the subsonic axial compressor and found that the BTR can increase the turbulent intensity near the casing and improve the SM of the compressor.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main casing treatment technologies include the circumferential groove casing treatment, the axial slot casing treatment, the self-circulating casing treatment (SCT), and so on. In the past scholars' research, Hembera et al 3 summarized and analyzed the research on the circumferential groove casing treatment done by Bailery et al [4][5][6][7][8][9][10][11][12] and found that while the casing treatment improves the stable working margin of the compressor, it is almost at the expense of compressor efficiency, and the efficiency loss is about 0.10-1.01%.Wilke and Kau 13,14 have done a lot of research on the improvement stability effect and mechanism of the casing treatment on different compressor models. The research mainly focuses on the circumferential groove casing treatment and the axial slot casing treatment on a transonic front stage of a modern high pressure compressor.…”
Section: Introductionmentioning
confidence: 99%